ANALISIS SWOT DALAM PERUMUSAN STRATEGI KEUNGGULAN BERSAING PADA UMKM BONO COFFEE SHOP DI TENGAH PERSAINGAN USAHA SEJENIS - I Wayan Eka Subandi; I Putu Dharmawan Pradhana (Bajang Institute, 2026)
Strategic management plays an important role in improving operational efficiency, optimizing resource utilization, and creating a competitive advantage through the right strategy. One of the methods used to formulate such a strategy is a SWOT analysis, which identifies the company's internal and external factors. This study aims to analyze the internal and external factors of Bono Coffee Shop MSMEs and formulate a competitive advantage strategy based on SWOT analysis. The research uses a qualitative descriptive approach with data collection techniques through observation, interviews, documentation, and literature studies. The research informants consisted of owners, employees, and customers of Bono Coffee Shop. Data analysis was carried out using IFAS and EFAS analysis, SWOT charts, and SWOT matrices. The results of the study show that Bono Coffee Shop has strengths in the form of friendly service, consistent product quality, comfortable atmosphere, strategic location, and affordable prices. The weaknesses include suboptimal promotions, limited facilities and capital, and product innovation that has not been maximized. Business opportunities come from the increasing trend of coffee shops and the development of social media, while the threat comes from the increasing competition of similar businesses. The results of the analysis showed an S−W value of 1.46 and O−T of 1.32, so that Bono Coffee Shop is in Quadrant I (Growth Strategy) with a Strengths-Opportunities (SO) strategy through improving product and service quality, digital promotion, product innovation, and expanding cooperation